TOTALLY IMPLANTABLE VENOUS ACCESS DEVICES IN ONCOLOGY: RETROSPECTIVE ANALYSIS OF 652 PATIENTS - Ferreira da Silva, Filipa (2020)
Introduction: Adequate venous access is essential for the treatment and management of cancer patients. Insertion of totally implantable venous access devices (TIVADs) provide a safe method for chemotherapy (ChT) administration, but it’s not free of complications. We aim to analyze our institution clinical practice experience regarding TIVADs. Materials and Methods: Electronic medical records (EMR) review of all cancer patients that required placement of a TIVAD at Hospital da Luz between January 1st 2008 and December 31st 2014. Results: Clinical data from 652 cancer patients was retrospectively reviewed. The overall incidence of complications was 14.1% (91), with only 6 (0.9%) being early complications (before the first clinical TIVAD utilization). The most common complications were thrombosis (30, 4.5%) and infections (TIVAD related and cutaneous, 24, 3.5%), followed by exteriorization (13, 1.9%) and catheter dysfunction (11,1.6%). 155 TIVADs were removed, the majority (95, 61.3%) because of end of treatment and the remainder (60; 38.7%) due to catheter complications. Discussion: Global complication rate was as expected, however we observed a low rate of early complications, and we didn’t observe any potentially fatal complication related to the procedure. Unlike expected, thrombotic complications were the most frequent, followed by infectious complications. Conclusions: TIVADs insertion is a safe procedure in cancer patients with an apparent low rate of complications with no fatal events identified in this study.